Hero dog! - Lysiak, Hilde 2006-; Lew-Vriethoff, Joanne; Lysiak, Matthew (New York, NY Branches/Scholastic Inc, 2017)
Nine-year-old Hilde Lysiak is an aspiring reporter with her own newspaper, the Orange Street News, and she is investigating break-ins and missing baked goods--and with the help of Zeus, a little dog with a big bark, she intends to track down the thief who is trying to steal a win in the Bake-Off Bonanza, one of Selinsgrove's biggest events
English stories
Reading level grade 2
Appeals to 2nd-3rd graders
2
Keywords: Detective and mystery stories; Dogs -- Juvenile fiction; Reporters and reporting -- Juvenile fiction; Theft -- Juvenile fiction; Dogs -- Fiction; Mystery and detective stories; Reporters and reporting -- Fiction; Stealing -- Fiction; Detective and mystery fiction; Mystery fiction